The Sun God Aliases in Paragraph (200bcd) from the Pyramid Texts - Amer, Islam Ibrahim.
A number of the aliases of the sun god Re have been recorded in the Pyramid Texts, each of which symbolized an epithet of the god Re. This paper will examine three aliases of the sun god Re in paragraph (200bcd) (Ndi; Pndn; Dndn)  from the Pyramid Texts, concerning which Egyptologists have quite various views. The paper aims at identifying the true meanings of the aliases, and their linguistic derivations, clarifying their religious significance as well as manifesting the solar epithets represented and symbolized by such aliases.